(untitled) (Biological Sciences - PJSIR, 2001)
Efficient methods for the preparation of pharmaceutical grade aescin, sodium aescinate and aescin polysul phate sodium salt from the carefully dried seeds of Aesculus indica Wallex Camb, HkF (Hippocastanaceae) have been described. The identity and puri ty of products was achieved through comparison with standards usin g potentiometric assay, HPLC, UV, IR, NMR spectroscopy and mass spectrometry.